Resposta da cultura da berinjela fertirrigada utilizando gotejamento com doses de nitrogênio e potássio em ambiente protegido - Souza, Álvaro Henrique Cândido de (2016)
The eggplant is a fruit vegetable that is part of exquisite menus, with important nutrients in food, and may even lower decrease cholesterol. Its cultivation is often realized in a greenhouse due to the advantages provided by the system. Fertigation allows rational use of fertilizers, water-saving, system automation and increased fruit quality. However, it is necessary to have technical knowledge about fertigation, because use excessive doses can reduce productivity and viability of the production system, primarily caused by soil salinity. We should know the dose that provides the highest productivity for each specific cultivation system. The objective of the present study was to evaluate the growth and eggplant crop yield when applied doses of nitrogen and potassium through fertigation in a greenhouse. We tested four nitrogen doses (0.0, 6.43, 12.86 and 25.72 g N plant-1) and potassium (0.0, 5.18, 10.36 and 20.73 g K plant- 1), totaling 16 treatments in a factorial arranged 4 x 4, in a completely randomized design with four replications. The doses were applied to cover fertigation, using urea and potassium chloride as a source of N and K respectively. The application of increasing doses of nitrogen promoted increase in productivity, number of fruits per plant, root dry mass, stem dry weight, total dry weight, plant height, stem diameter and total leaf area. Increases in potassium levels not statistically influenced the productivity of the crop. The dose provided higher productivity and number of fruits per plant eggplant is between the range 14.0 to 17.0 g N plant-1 (145-177 kg N ha-1).